Molecular cloning and characterization of the vasopressin-regulated urea transporter of rat kidney collecting ducts. - Shayakul, C (1996)
Absorption of urea in the renal inner medullary collecting duct (IMCD) contributes to hypertonicity in the medullary interstitium which, in turn, provides the osmotic driving force for water reabsorption. This mechanism is regulated by vasopressin via a cAMP-dependent pathway and activation of a specialized urea transporter located in the apical membrane. We report here the cloning of a novel urea transporter, designated UT1, from the rat inner medulla which is functionally and structurally distinct from the previously reported kidney urea transporter UT2. UT1 expressed in Xenopus oocytes mediated passive transport of urea that was inhibited by phloretin and urea analogs but, in contrast to UT2, was strongly stimulated by cAMP agonists. Sequence comparison revealed that the coding region of UT1 cDNA contains the entire 397 amino acid residue coding region of UT2 and an additional 1,596 basepair-stretch at the 5' end. This stretch encodes a novel 532 amino acid residue NH2-terminal domain that has 67% sequence identity with UT2. Thus, UT1 consists of two internally homologous portions that have most likely arisen by gene duplication. Studies of the rat genomic DNA further indicated that UT1 and UT2 are derived from a single gene by alternative splicing. Based on Northern analysis and in situ hybridization, UT1 is expressed exclusively in the IMCD, particularly in its terminal portion. Taken together, our data show that UT1 corresponds to the previously characterized vasopressin-regulated urea transporter in the apical membrane of the terminal IMCD which plays a critical role in renal water conservation.